Polarized Vascular Endothelial Growth Factor Secretion by Human Retinal Pigment Epithelium and Localization of Vascular Endothelial Growth Factor Receptors on the Inner Choriocapillaris : Evidence for a Trophic Paracrine Relation - Blaauwgeers, Harriët G. T. (American Society for Investigative Pathology, 1999)
The retinal pigment epithelium (RPE) maintains the choriocapillaris (CC) in the normal eye and is involved in the pathogenesis of choroidal neovascularization in age-related macular degeneration. Vascular endothelial growth factor-A (VEGF) is produced by differentiated human RPE cells in vitro and in vivo and may be involved in paracrine signaling between the RPE and the CC. We investigated whether there is a polarized secretion of VEGF by RPE cells in vitro. Also, the localization of VEGF receptors in the human retina was investigated. We observed that highly differentiated human RPE cells, cultured on transwell filters in normoxic conditions, produced two- to sevenfold more VEGF toward their basolateral side as compared to the apical side. In hypoxic conditions, VEGF-A secretion increased to the basal side only, resulting in a three- to 10-fold higher basolateral secretion. By immunohistochemistry in 30 human eyes and in two cynomolgus monkey eyes, KDR (VEGFR-2) and flt-4 (VEGFR-3) were preferentially localized at the side of the CC endothelium facing the RPE cell layer, whereas flt-1 (VEGFR-1) was found on the inner CC and on other choroidal vessels. Our results indicate that RPE secretes VEGF toward its basal side where its receptor KDR is located on the adjacent CC endothelium, suggesting a role of VEGF in a paracrine relation, possibly in cooperation with flt-4 and its ligand. This can explain the known trophic function of the RPE in the maintenance of the CC and its fenestrated permeable phenotype and points to a role for VEGF in normal eye functioning. Up-regulated basolateral VEGF secretion by RPE in hypoxia or loss of polarity of VEGF production may play a role in the pathogenesis of choroidal neovascularization.